Recent progress in silicon-based millimeter-wave power amplifier - Han, Jiang An (2013)
This paper reports the recent research advancements in silicon-based millimeter-wave solid-state power amplifier (PA). It provides an in-depth overview that facilitates PA designers to select a suitable silicon-based topology based on the vital aspects of process and design technique. The crucial active devices used for fabrication including standard CMOS, CMOS SOI, SiGe BiCMOS and GaN on SiC are introduced. The state-of-the-art architectures for power combining are compared in terms of power delivered, power added efficiency (PAE), bandwidth and reflection coefficient. A major emphasis is placed on the 60 GHz solid-state PAs, as it is the driving force in silicon-based RFIC development.